A Fair Globalization: Effects on Global Economic Growth, Creating Opportunities for all - Onyemachi; Adanso, Chidinma; Osim; Oru, Chinomso; Igwe, Dr. A. A. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The goal of this study is to ascertain the extent to which fair globalization affects the expansion of the world economy and opens up opportunities for everyone. Therefore, the specific aims of this article are to ascertain the influence of employee motivation on global productivity in a fair globalization, assess the impact of overlapping membership in multinational countries on multilateral trade and investment in a fair globalization, and evaluate the effects of new information and communication technologies. The main effects of unfair globalization include restrictions on the free flow of ideas and information, restrictions on capital flows, and restrictions on the export of goods. A volume of the International Labour Organization's published report collected by the world commission on the social Dimension of Globalization along with other documents, was used as a secondary source of data in the methodology. This study revealed the urgent need for a rethink of global governance structures and policies as well as the necessity to create a fair and inclusive globalization as a global priority. The International Labour Organization (ILO), an organization that upholds the fundamental human rights of the working class, supports the findings of the world commission on the social impact of globalization.